Leptin promotes a proinflammatory lipid profile and induces inflammatory pathways in human SZ95 sebocytes. (1st December 2014) - Törőcsik, D.; Kovács, D.; Camera, E.; Lovászi, M.; Cseri, K.; Nagy, G.G.; Molinaro, R.; Rühl, R.; Tax, G.; Szabó, K.; Picardo, M.; Kemény, L.; et al.
Summary: Background: Leptin, the adipocyte‐secreted hormone that regulates weight, is known to link lipid metabolism with inflammation in various cell types. However, its role in human sebocytes has not yet been investigated. Objectives: The purpose of this study was to investigate the effects of leptin in human sebaceous gland biology. Methods: Expression of the long form of the leptin receptor (Ob‐Rb) was detected by real‐time quantitative reverse transcriptase polymerase chain reaction (qRT‐PCR) and immunochemistry. Lipid analysis was by high‐performance thin‐layer chromatography, gas chromatography–mass spectrometry and time‐of‐flight mass spectrometer mass detection. Lipid bodies were visualized by BODIPY staining using fluorescent microscopy and measured by flow cytometry. Interleukin (IL)‐6 and IL‐8 mRNA levels were assessed by real‐time qRT‐PCR and their release was evaluated by enzyme‐linked immunosorbent assay. Cyclooxygenase (COX)‐2 and 5‐lipooxygenase (LOX) protein expression and phosphorylation of p65 and signal transducer and activator of transcription (STAT)‐3 were determined by Western blot analysis. Results: Expression of Ob‐Rb was detected in human sebaceous glands and in cultured human SZ95 sebocytes. The treatment of SZ95 sebocytes with leptin led to enlarged intracellular lipid bodies, increased ratios of unsaturated/saturated fatty acids and decreased vitamin E levels. Further supporting a proinflammatory role, leptin induced COX‐2 and 5‐LOX expression in SZ95 sebocytes and augmented the production of IL‐6 and IL‐8 cytokines. On leptin treatment, the STAT‐3 and nuclear factor‐κB pathways were activated, indicating that these known leptin signalling pathways are active in human sebocytes. Conclusions: Our findings suggest that leptin signalling may be involved in the proinflammatory regulation of sebaceous lipid metabolism and the induction of inflammatory enzymes and cytokines.